PENGARUH HAR GA TERHADAP KEPUTUSAN PEMBELIAAN PADA RESTORAN SHUKAKU DI KOTA GARUT - Agil, Agil Erdiansyah; Ramayani Yusuf2; Rohimat Nur Hasan (Universitas Haji Sumatera Utara, 2023)
This study aims to determine the partial effect of price on purchasing decisions at Shukaku restaurants in the city of Garut. For the sampling technique using nonprobability sampling, with the type of accidential sampling method. The data collection technique uses a questionnaire with a Likert scale, each of which has been tested and meets the requirements of validity and reliability. The data analysis technique used in this study is simple linear regression. The results of the research on simple linear regression analysis show that the price variable simultaneously has a positive influence on purchasing decisions. This can be proven from the calculated F value of 178.031 with a Sig value of 0.000, meaning that the significance value is less than the probability value (0.000 < 0 ,1) so that it can be concluded that the price has a significant effect on purchasing decisions.